Bibliometric analysis by exploring digital adoption in small and medium-sized enterprises (SMEs): A global review / Ira Syazwani Mohamad Marzuki, Kamaruddin Othman and Hafizah Hammad Ahmad Khan - Mohamad Marzuki, Ira Syazwani; Othman, Kamaruddin; Ahmad Khan, Hafizah Hammad (Research Management Centre (RMC), 2023)
The objective of this study was to examine peer-reviewed literature on the adoption of digital technologies among Small and Medium-Sized Enterprises (SMEs) on a global scale. A bibliometric analysis methodology was used. For the study period spanning from 1995 to 2022, documents from peer-reviewed journals focusing on the adoption of digital technologies among Small and Medium-Sized Enterprises (SMEs) were retrieved using the Scopus database. A total of 267 documents were retrieved. The most productive authors and institutions in this subject area are in the United States, the United Kingdom, Australia, and Malaysia. The application of keyword clustering analysis revealed that the primary areas of research within the field of digital transformation encompass information and communication technology, as well as Small and Medium Enterprises. The study acknowledges the constraints pertaining to the scope of motivations investigated and the extent to which the sample is representative. To address these limitations, further research is recommended to explore different motives and verify the findings through the use of diverse samples. This study contributes to the existing body of knowledge by offering empirical evidence on the adoption of digital technologies in Small and Medium-Sized Enterprises (SMEs), thereby deepening the understanding of the extent of digital adoption